2022
DOI: 10.3345/cep.2020.01620
|View full text |Cite
|
Sign up to set email alerts
|

Global relationship between parent and child obesity: a systematic review and meta-analysis

Abstract: Global relationship between parent and child obesity: a systematic review and meta-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 46 publications
4
28
0
Order By: Relevance
“…Many studies have indicated an association between the body mass category of a parent and that of their child, but the underlying mechanisms are not well established [ 50 , 51 , 52 ]. Evidence suggested that BMI and obesity are strongly correlated among biological parent-child pairs, but there are no significant intergenerational associations in these health traits among adoptive parent-child pairs [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have indicated an association between the body mass category of a parent and that of their child, but the underlying mechanisms are not well established [ 50 , 51 , 52 ]. Evidence suggested that BMI and obesity are strongly correlated among biological parent-child pairs, but there are no significant intergenerational associations in these health traits among adoptive parent-child pairs [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between excess weight of parents and children was higher in Asia than in Europe and the Middle East, as well as higher in high-income countries than in middle- or low-income countries. Furthermore, a stronger correlation was observed between excess weight from parents and children when both parents were obese than when only one of the parents was obese [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The family environment can affect the child's nutrition and physical activity habits; negative attitudes and behaviors can pave the way for the development of an obesogenic environment ( 6 ). For this reason, it is of utmost importance to children's nutritional habits to analyze the dynamics related to parental factors, diagnose and treat childhood obesity in the early period, and prevent adulthood obesity ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Parental behaviors and the home environment are the most effective ways to acquire healthy eating and active lifestyles associated with eating habits and obesity ( 7 , 8 ). This effect might occur directly and indirectly, and the family's attitudes, behaviors, and beliefs play a role in this interaction ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicates a strong relationship between parental (maternal, paternal, or both) obesity and offspring obesity [ 6 ]. In a very recent issue of Clinical and Experimental Pediatrics , Lee et al [ 7 ] reviewed relationship between parental (maternal, paternal, or both) obesity and offspring obesity. Additionally, parental education level, parental smoking status, parental employment status, monthly familial income, and number of household members are closely related to obesity [ 8 ].…”
mentioning
confidence: 99%